Renovascular Hypertension: Pathophysiology, Diagnosis, and Treatment - Black, Henry R. (1978)
Renovascular hypertension can result from renal artery lesions involving the main renal artery, or its branches. It is generally felt that the elevation of blood pressure results from excessive systemic vasoconstriction secondary to enhanced renin secretion by one or part of one kidney. Renin secretion is enhanced because of constriction of the renal artery and resultant intrarenal ischemia. Clinically patients cannot be distinguished from those with essential hypertension and diagnosis must be made with arteriography although urography and isotope renography may suggest the diagnosis. Surgical cure can be predicted if differential renal vein renin ratios lateralize but a non-lateralizing study does not necessarily mean that surgery will fail. In properly selected patients, surgical results are excellent.